Gamma heavy chain disease associated with T-cell large granular lymphocyte lymphoproliferative disorder: case report and literature review. - Maria Laura Bisegna; Maria Assunta Limongiello; Stefano Fiori; Maria Stefania De Propris; Irene Della Starza; Stefania Trasarti (Mediterranean Journal of Hematology and Infectious Diseases)
Heavy chain diseases are rare B-cell neoplasms consisting of the production of a monoclonal immunoglobulin composed of the only heavy chain without corresponding light chains. It is a rare adult disease that may involve several sites with a variable clinical course. It manifests itself on a large spectrum from indolent to rapidly progressive. We present a case of heavy chain disease and concomitant T- cell large granular lymphoproliferative disorder, an association described in only six cases before.